Advanced nitrogen removal from low carbon nitrogen ratio domestic sewage via continuous plug-flow anaerobic/oxic/anoxic system: Enhanced by endogenous denitrification. (June 2023) - Liu, Huaguang; Dong, Wenyi; Zhao, Zilong; Wang, Hongjie; Hou, Zilong; Li, Yanchen; Zeng, Zhiwei; Xie, Jin; Wang, Fupeng; Liu, Xueyon; Yan, Yu; Qu, Yanhui
Graphical abstract: Highlights: Effluent TIN 7.9 ± 2.2 mg N/L was obtained from low COD/TIN (2.9 ± 0.4) sewage. Endogenous denitrification and SND removed 38% and 15% of the TIN. The specific endogenous denitrification rate was quantified as 0.4 mg N/g MLSS‧h. Low dissolved oxygen concentration and short HRToxic = 3 h could save energy. Abstract: An anaerobic/oxic/anoxic continuous plug-flow biorereactor was established to derive stable advanced nitrogen removal of oligotrophic domestic wastewater by setting a sludge dual-reflux system and a mixed liquid cross-flow system, while extending the hydraulic retention time in anoxic section. The effluent total inorganic nitrogen was 7.9 ± 2.2 mg N/L, with removal efficiency of 84 ± 3.9%. Results of nitrogen balance calculations indicated that the contribution of simultaneous nitrification and denitrification to total inorganic nitrogen loss in oxic region was 15% during stable stage, and the total inorganic nitrogen removal by endogenous-denitrification and enhanced exogenous-denitrification in the anoxic region was 39.9%. Prolongation of hydraulic retention time in anoxic segment is the critical reason for enhancing endogenous-denitrification, and cross-flow system is an important measure to improve exogenous-denitrification. This study provides new insights into bridging the gap between energy-saving and high-level nitrogen removal from municipal wastewater with low carbon to nitrogen ratios.